(untitled) (The Research of Medical Science Review, 2024)
Teeth whitening is a cosmetic treatment getting popularity all over the world. This quantitative study aimed to investigate the efficacy of different teeth whitening methods and their impact on tooth enamel. A total of 150 participants were randomly assigned to one of five groups: hydrogen peroxide (HP), carbamide peroxide (CP), sodium bicarbonate (SB), LED light-activated whitening (LED), and a control group. Tooth shade and enamel hardness were measured at baseline, after treatment, and at a 2-week follow-up. Results showed that HP and CP groups demonstrated significant tooth whitening (p < 0.001) with minimal enamel hardness changes. LED group showed moderate whitening (p < 0.01) with slight enamel hardness reduction. SB group showed minimal whitening (p > 0.05) with no significant enamel hardness changes. The control group showed no significant changes. This study suggests that HP and CP are effective teeth whitening methods with minimal impact on tooth enamel.